Comparative performance evaluation of a porous radiant burner with a conventional burner: Biogas combustion. (5th January 2023) - Devi, Sangjukta; Sahoo, Niranjan; Muthukumar, P
Highlights: Crude biogas combustion between novel SFPRB and CB has been investigated. Heat transfer enhancement is achieved via two-layer porous ceramic (SiC and Al2 O3 ) SFPRB can operate on lean combustion, while CB functions in rich fuel condition. SFPRB offers maximum energy saving of 38% and reduction of CO by 95% and NOx by 85% Abstract: The aim of present research is to conduct a comparative performance analysis of a newly developed Sideway Faced Porous Radiant Burner (SFPRB), with a commercially available Conventional Burner (CB). Both the burners have been fuelled by crude biogas. Comparative study of both the burners have been done in terms of thermal and combustion efficiencies and pollutant emissions. The SFPRB is composed of Alumina (Al2 O3 ) and Silicon Carbide (SiC) porous matrices. Biogas generated from anaerobic digestion of cow dung, consisting majorly of 43–56% methane (CH4 ) and 34–38% carbon dioxide (CO2 ), was used as fuel during investigation. Combustion in SFPRB was found to be stable in the equivalence ratio range of 0.75–0.97, while CB works in rich fuel condition at an equivalence ratio of 1.38. In order to get an insight in to the combustion behaviour of SFPRB, temperatures in both axial and radial directions have been measured. The performance comparison of SFPRB with CB have been done within the firing rates of 442–884 kW/m 2 . Maximum percentage improvement in thermal efficiency of ∼ 38% is achieved with SFPRB. The measured emission values from SFPRB have been always lower than CB. The SFPRB emitted maximum CO and NOx, 165 ppm and 8.2 ppm respectively; while CB emitted higher values, 3276 ppm and 27 ppm respectively. The present experimental investigation confirmed that SFPRB delivered superior performance at all test cases. The findings from the present research work provides an insight into the development of an energy efficient and clean burner for crude biogas application.